Sistem Informasi Pengelolaan Keuangan BLUD Pada Puskesmas Kuala Tungkal I - Rambe, Maulana Tua; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2022)
The BLUD (Badan Layanan Umum Daerah) financial management system at Puskesmas Kuala Tungkal 1 is not optimal. The problem with cash book transactions is a journalizing feature is not working. Penatausaha can't control the realization budget and financial reports. The research objective was to design a BLUD financial management information system in Puskesmas Kuala Tungkal 1, Tanjabbar Regency. System development with prototype modeling and tools using Unified Modeling Language (UML); use case diagrams, activity diagrams, class diagrams, and flowchart diagrams. As a result, the interface design for budget planning, cash receipts and disbursements transactions, cash journaling, and financial reports. Recommendation; create a journalizing function, you should adjust the government financial accounting standards.